Transcriptional regulation of a gonococcal gene encoding a virulence factor (L-lactate permease). - Julio C Ayala; William M Shafer (PLoS Pathogens, 2019)
GdhR is a GntR-type regulator of Neisseria gonorrhoeae encoded by a gene (gdhR) belonging to the MtrR regulon, which comprises multiple genes required for antibiotic resistance such as the mtrCDE efflux pump genes. In previous work we showed that loss of gdhR results in enhanced gonococcal fitness in a female mouse model of lower genital tract infection. Here, we used RNA-Seq to perform a transcriptional profiling study to determine the GdhR regulon. GdhR was found to regulate the expression of 2.3% of all the genes in gonococcal strain FA19, of which 39 were activated and 11 were repressed. Within the GdhR regulon we found that lctP, which encodes a unique L-lactate transporter and has been associated with gonococcal pathogenesis, was the highest of GdhR-repressed genes. By using in vitro transcription and DNase I footpriting assays we mapped the lctP transcriptional start site (TSS) and determined that GdhR directly inhibits transcription by binding to an inverted repeat sequence located 9 bases downstream of the lctP TSS. Epistasis analysis revealed that, while loss of lctP increased susceptibility of gonococci to hydrogen peroxide (H2O2) the loss of gdhR enhanced resistance; however, this GdhR-endowed property was reversed in a double gdhR lctP null mutant. We assessed the effect of different carbon sources on lctP expression and found that D-glucose, but not L-lactate or pyruvate, repressed lctP expression within a physiological concentration range but in a GdhR-independent manner. Moreover, we found that adding glucose to the medium enhanced susceptibility of gonococci to hydrogen peroxide. We propose a model for the role of lctP regulation via GdhR and glucose in the pathogenesis of N. gonorrhoeae.